The role of complement in normal pregnancy and preeclampsia - Burwick, Richard M.; Java, Anuja; Regal, Jean F. (Frontiers in Immunology, 2025)
Preeclampsia affects 3-4% of pregnancies with adverse effects for both mother and child. Minimal therapeutic options are available, and biomarkers are urgently needed to identify those at greatest risk early in the pregnancy. Both the innate and adaptive immune systems are well regulated during normal pregnancy including the complement system. A functioning complement system with some degree of complement activation participates in proper placental development, ensuring a healthy pregnancy and assisting with host defense. However, aberrant complement activation can lead to adverse pregnancy outcomes such as preeclampsia. An overview of the complement system will be presented, along with review of the pre-clinical literature in animal models providing evidence for complement involvement in maintaining a normal pregnancy and contributing to symptoms of preeclampsia. In addition, clinical studies with evaluation of complement biomarkers in plasma and urine implicate complement dysregulation in the pathophysiology of subtypes of preeclampsia including HELLP (hemolysis, elevated liver enzymes and low platelet count) syndrome. Recent studies on the genetics of complement dysregulation in preeclampsia will be reviewed, along with updates on use of recently developed complement therapeutics. The potential utility of evaluating complement activation or manipulating complement during pregnancy will be discussed in view of the successful use of complement therapeutics in pregnancy in other immune diseases.